Surface velocities and calving flux of the Academy of Sciences Ice Cap, Severnaya Zemlya - P. Sánchez-Gámez; F. J. Navarro; J. A. Dowdeswell; E. De Andrés (Лëд и снег, 2020)
We have determined the ice-surface velocities of the Academy of Sciences Ice Cap, Severnaya Zemlya, Russian Arctic, during the period November 2016 – November 2017, using intensity offset-tracking of Sentinel-1 synthetic-aperture radar images. We used the average of 54 pairs of weekly velocities (with both images in each pair separated by a12-day period) to estimate the mean annual ice discharge from the ice cap. We got an average ice discharge for 2016–2017 of 1,93±0,12 Gt a−1, which is equivalent to −0,35±0,02 m w.e. a−1 over the whole area of the ice cap. The difference from an estimate of ~1,4 Gt a−1 for 2003–2009 can be attributed to the initiation of ice-stream flow in Basin BC sometime between 2002 and 2016. Since the front position changes between both periods have been negligible, ice discharge is equivalent to calving flux. We compare our results for calving flux with those of previous studies and analyse the possible drivers of the changes observed along the last three decades. Since these changes do not appear to have responded to environmental changes, we conclude that the observed changes are likely driven by the intrinsic characteristics of the ice cap governing tidewater glacier dynamics.